Child and family-related characteristics and early childhood education attendance of second graders with reading difficulties - Corales, Neil Christian T.; Roldan, Aurorita T. (Quezon City College of Home Economics, University of the Philippines Diliman, 2017)
This study aimed to explore on child and family related factors as well as the early childhood education attendance of selected second graders perceived to have reading difficulties by their teachers. Purposive sampling was used in identifying 30 children with reading difficulties through their teachers, while random sampling was used to choose their 30 counterpart children for the control group. A total of 60 parents and five teachers of the sampled children were interviewed to gather data. Chi-square (𝑥2) test was used to determine the variables that are statistically significant to the second graders reading difficulties. On the other hand, qualitative data were analyzed on the basis of recurring patterns and themes. Results showed that the perceived reading difficulties of the second graders by their teachers were: (a) recognition of letter as well as their sounds, (b) recognition of words in English those with consonant cluster and blends, and (c) recognition of basic sight words, and (d) recognition of words in Ilokano, Filipino, and English. Behavioral characteristics of pupils with reading difficulties were inattentiveness, short attention span, dependence on classmates, distracting classmates, and not engaging in class activities. Significant family-related characteristics related to pupil's reading difficulties were presence of family members with reading difficulties and home literacy environment like availability of reading difficulties, presence of persons teaching the child to read at home, frequency of teaching reading of the child at home, and reading stories to the child. Significant characteristics in terms of early childhood education attendance was child's age of entry.
submitted June 2017
Thesis (Master of Family Life and Child Development)--University of the Philippines Diliman.
Keywords: Reading disability -- Philippines; Education, Primary -- Parent participation